Vegan for her : the women's guide to being healthy and fit on a plant-based diet - Messina, Virginia (Da Capo Lifelong, a member of the Perseus Books Group, 2013)
"Can you meet your calcium needs if you're only eating plant-based foods? Is a vegan pregnancy safe? What about the link between soy foods and breast cancer? How does a plant-based diet affect weight loss, aging, and fertility? In Vegan for Her, dietitian Virginia Messina tackles the issues most pertinent to women who follow or who are considering a vegan diet, and JL Fields provides health-supportive recipes and tips for taking your veganism beyond the plate. With specific guidance on meeting women's unique nutritional needs throughout the lifecycle and information about food choices that relate to many health concerns, Vegan for Her is a practical and realistic guide to making sure your plant-based diet is as healthy as it can be"--Provided by publisher.